Alzheimer’s Assistant Using Arduino (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The increasing prevalence of Alzheimer's disease among the elderly has spurred efforts to develop innovative solutions for patient care and monitoring. This project proposes a comprehensive system, embodied in a wearable device, designed to monitor the health status of Alzheimer's patients. The device integrates sensors such as GPS for location tracking, a gyroscope for detecting sudden movements, and sensors for measuring vital signs including body temperature, heart rate, and blood oxygen saturation (SpO2). Data collected by the sensors is transmitted in real time to caregivers or healthcare professionals using IoT and the Blynk platform, ensuring prompt responses to emergencies or irregularities. The system aims to enhance patient safety by providing continuous updates on their health and location, reducing risks associated with wandering or sudden health declines. The sensors are seamlessly connected to microcontrollers, including Arduino Nano and NodeMCU ESP8266, which facilitate data processing and communication. The project's results demonstrate accurate performance, offering a scalable solution for managing Alzheimer's patients. The use of low-power sensors ensures energy efficiency, making the device practical for prolonged use. This innovative system highlights the potential of integrating IoT and wearable technologies to improve the quality of life for patients and their families.